Towards a sustainable soil fertility strategy in Ghana: Report submitted to the Ministry of Food and Agriculture Government of Ghana - Jayne, Thomas S.; Kolavalli, Shashidhara; Debrah, Kofi; Ariga, Joshua; Brunache, Pierre; Kabaghe, Chance; Nunez-Rodriguez, Walter; Owusu Baah, Kwaku; Bationo, Andre A.; Huising, Elzo Jeroen; Lambrecht, Isabel B.; Diao, Xinshen; et al. (International Food Policy Research Institute, 2015)
Most efforts to raise fertilizer use in SSA over the past decade have focused on fertilizer subsidies and targeted credit programmes with hopes that these programmes could later be withdrawn once the profitability of fertilizer use has been made clear to adopting farmers and once they have become sufficiently capitalized to be able to afford fertilizer on their own. This line of reasoning under-emphasizes the evidence that many smallholder farmers obtain very low crop response rates to inorganic fertilizer application and hence cannot use it profitably at full market prices. A central hypothesis of this study is that Ghanaian farmers will demand increasing quantities of fertilizer when they can utilize it more profitably, and that doing so will require improved agronomic and soil management practices that enable farmers to achieve higher crop response rates to fertilizer application. The study’s findings are based on reviews of existing studies from Ghana and the wider region, key informant interviews of cocoa and maize farmers, international and local scientists, fertilizer distribution companies and government officials.